Current Ratio, Debt to Equity Ratio and Total Assets Turnover to Company Value Mediated by Return On Equity - Juliyani, Devi; Gularso, Kurnadi (Pelopor Publikasi Akademika, 2023)
This research aims to determine the effect of current ratio, debt to equity ratio, and total assets turnover on company value which is mediated by return on equity studies on basic materials sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research technique was carried out using purposive sampling with a sample of 36 manufacturing companies that published financial reports and were listed on the Indonesia Stock Exchange for the 2018-2022 period. Testing in this research was carried out with the Eviews 9 software program. The results of the research show that there is no significant influence of the current ratio on firm value, there is a significant positive influence of the debt to equity ratio on firm value, there is no significant influence of total assets turnover on firm value, there is no significant influence of the current ratio on return on equity, there is an influence significant negative effect of debt to equity ratio on return on equity, there is no significant effect of total assets turnover on return on equity, there is a significant positive effect of return on equity on firm value, there is no significant effect of current ratio on firm value mediated by return on equity, There is a significant influence of debt to equity ratio on firm value which is mediated by return on equity, there is no significant influence of total assets turnover on firm value which is mediated by return on equity